PERENCANAAN PEMBANGUNAN NASIONAL MODEL GBHN - Siti Marwiyah (Faculty of Law, University of Dr. Soetomo, 2017)
The idea of reviving the National Guidelines of State Policy (GBHN) rests on the assumption that development in Indonesia is uncertain or unplanned. This paradigm resulted in the development of no or less on target and failed to show its maximum.